Internal stress controls tendril writhing dynamics in climbing plants - Émilien Dilly; Julien Derr; Dražen Zanchi (Proceedings of the National Academy of Sciences, 2026)
We present experimental results on the writhing dynamics of cucumber plant tendrils subjected to an axial traction force. At low forces, the tendrils’ curvature saturates exponentially in time at a limiting value. At forces higher than the critical threshold, the tendril fails to coil but develops an intrinsic coiling-prone stress, corresponding to an intrinsic residual curvature, visible if the load is released. Growth-field assessments indicate that curvature arises from differential growth. To understand these experiments we develop an autotropic morphoelastic growth model with a bi-strip geometry, in which one strip undergoes mechanosensitive growth. In the absence of an external load, curvature generation is solely limited by internal stresses. To link the actual curvature to a finite external force, the tendril is approximated as a Kirchhoff rod. The resulting model reproduces the two observed regimes: below the critical axial force, the tendril coils, and above this force, the tendril remains straight but still exhibits intrinsic curvature.